PENGARUH INDEPENDENSI DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT: Studi empiris pada kantor Inspektorat Kota Sungai Penuh - Rio Baviga (Gapenas Publisher, 2022)
This study aims to determine the effect of auditor independence and ethics on audit quality. An empirical study at the Sungai Senuh City inspectorate office partially and simultaneously. Respondents of this study were 33 people who were auditors in the city inspectorate of Sungai Penuh. The instrument in this study has passed the Validity and Reliability test stages, by performing multiple regression tests, coefficients of determination, F statistic test (simultaneous) t statistical test (partial). The result of this study is that independence has no relationship to audit quality. This is evidenced by tcount < ttable (1.180 < 1.701) and significant <0.05 (0.248 <0.05) meaning that there is no influence between independence on audit quality. Auditor ethics has a relationship with audit quality. This is evidenced by tcount > ttable (3.090 > 1.701) and significant <0.05 (0.04 <0.05) meaning that there is an influence between auditor ethics on audit quality. Simultaneously, the independence and ethics of auditors on audit quality is evidenced by Fcount > Ftable or (17.7655 > 3.34), and with a significant value = 0.000 <0.05 then H0 is rejected and Ha is accepted, meaning that there is an influence between independence and auditor ethics on audit quality at the full river city inspectorate office. The magnitude of the influence of auditor independence and ethics on audit quality simultaneously is 55, 8%